Determinants of Savings and Loan Cooperative Development: The Role of Member Participation and Financial Literacy - Nirwana, Ida; Sriyanti, Esy; Andreskhi, Fadri (Journal of International Accounting, Taxation and Information Systems, 2025)
Despite their vital role in community empowerment, many cooperatives encounter challenges arising from low levels of member participation and inadequate financial literacy. These issues often hinder the effectiveness and sustainability of cooperative operations. As such, the purpose of this study was to determine the extent of the Influence of Member Participation and Financial Literacy on Cooperative Development at the Ibu Mandiri Berprestasi Cooperative, Palangki Village, Sijunjung Regency. This quantitative study involved a population consisting of 48 cooperative members. The study employed a total sampling approach for participant selection and collected data through questionnaires. The finding showed that Member Participation (X1) significantly influences Cooperative Development. Similarly, Financial Literacy (X2) demonstrated a significant impact on Cooperative Development. The F-test results indicated that both Member Participation and Financial Literacy collectively influence Cooperative Development in a statistically significant manner. The findings emphasize the need to increase member participation as well as financial literacy in order to reinforce cooperative development and guarantee durability.